Technology and medical sciences–TMSi 2010 : proceedings of the 6th International Conference on Technology and Medical Sciences–TMSi 2010, Porto, Portugal, 21-23 October 2010 /: proceedings of the 6th International Conference on Technology and Medical Sciences–TMSi 2010, Porto, Portugal, 21-23 October 2010. (©2011) - Unknown
No abstract available